Multi-drug Resistant Tuberculosis (MDR-TB) and Short Course Regimen Treatment Outcome at Maharaj Nakhonrachasima Hospital - กมลวัทน์, อติภา (Disease Control Journal, 2008)
This research aim to study situation of anti-tuberculosis drug resistance, short course regimen treatment outcome and factor associated with Multi-drug Resistant Tuberculosis (MDR-TB) at Maharaj Nakhonrachasima Hospital. This study was cross -sectional. Data was collected from laboratory tuberculosis register books and treatment cards during 1 January- 30 December 2007.Nighty-seven TB smear positive cases were enrolled. Culture and drug sensitivity test were performed. All received diagnostic counseling test (DCT) for HIV. 71.7% were male, mean aged 49.5 year S.D. = 16.87, 77.3% new TB cases, and 82.5% was HIV negative. The result revealed that resistance to any or more drugs was 16.5% (16/97), resistance to one drug was 6.2 %( 6/97), two drugs were 4.1%(4/97), three drugs were 4.1% (4/97) and four drugs were 2.1%(2/97). Resistance to at least Isoniazid and Rifampicin (MDR-TB) was 7.2%(7/97). The history of previously treated was significantly associated with MDR-TB (OR =5.33, 95% CL 1.09-5.33 p-value=0.05). Treatment outcome for those who defaulted more than 2 consecutive months or failure were associated significantly with MDR-TB (p-value=0.0016). But for sputum conversion rate did not associate with MDR-TB significantly.